2020
DOI: 10.1021/acscatal.0c03986
|View full text |Cite
|
Sign up to set email alerts
|

Regiodivergent Oxidative Cross-Coupling of Catechols with Persistent tert-Carbon Radicals

Abstract: Oxidative cross-coupling is a powerful synthetic strategy for forming a carbon−carbon bond from two nucleophiles having C−H bonds. However, controlling the coupling selectivity (homovs cross-coupling) and the chemo-(C−C vs C−O) and regioselectivity in the reaction of two distinct enolizable substrates under aerobic conditions is notoriously challenging. Here, we present a regiodivergent oxidative cross-coupling reaction between catechols and carbonyl compounds (2-oxindoles and benzofuranones). The oxidative cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 105 publications
0
28
0
Order By: Relevance
“…We identified that when using O 2 as an electron acceptor to trigger the SET process there was a 92% yield of dimerization product 77 † (Scheme 3d). 16 The control experiments confirmed the essential roles of n Bu 4 NI, the electron acceptor O 2 , and irradiation in the reaction. When the radical inhibitor TEMPO was added to this reaction, no cross-coupling product 3 was obtained (Scheme 3e).…”
Section: Resultsmentioning
confidence: 61%
“…We identified that when using O 2 as an electron acceptor to trigger the SET process there was a 92% yield of dimerization product 77 † (Scheme 3d). 16 The control experiments confirmed the essential roles of n Bu 4 NI, the electron acceptor O 2 , and irradiation in the reaction. When the radical inhibitor TEMPO was added to this reaction, no cross-coupling product 3 was obtained (Scheme 3e).…”
Section: Resultsmentioning
confidence: 61%
“…29) To characterize the TSs in open-shell Ni-catalyzed systems, we have employed a combined experimental and computational approach, [5][6][7] in which the simulated spectra of the catalyst, reactants, and products in the ground state are assessed by comparing various experimentally obtained spectra. 30,31) For example, on the basis of a series of earlier structural analyses [IR, UV, and electronic circular dichroism (ECD)] in tetrahydrofuran (THF), we concluded that Ni(II)-3a-(OAc) 2 is more stable in the triplet state than the singlet state. 5) Crucially, DFT calculations of Ni(II)-3a-(OAc) 2 in the triplet configuration reproduced the features in the spectroscopic analyses, including (i) the unique carboxylate shifts (1598 and 1558 cm −1 ) in the IR spectrum, (ii) broad bands of pseudo-octahedral structure of Ni(d 8 ) (408, 753, and 1182 nm) in the UV/Vis spectrum, and (iii) strong intensities in the near-IR region of the ECD spectra.…”
Section: Resultsmentioning
confidence: 99%
“…The high electron density is located at the 3-position, and upon single-electron oxidation, a persistent tertiary radical species is formed that dimerizes into bis-oxindoles (Scheme A) . Sohtome and Sodeoka demonstrated that bis-3-aryloxindoles are thermodynamically unstable and undergo regio-divergent oxidative cross-coupling with catechols (Scheme A) . In a different study, the Pietruszka group reported that N -Boc-3-aryloxindoles can be directly coupled with catechols using laccase catalysis …”
Section: Introductionmentioning
confidence: 99%
“…14 Sohtome and Sodeoka demonstrated that bis-3-aryloxindoles are thermodynamically unstable and undergo regio-divergent oxidative cross-coupling with catechols (Scheme 1A). 15 In a different study, the Pietruszka group reported that N-Boc-3aryloxindoles can be directly coupled with catechols using laccase catalysis. 16 N-Methyl-(3-aryl-and 3-benzyl-)oxindoles were found to react with anisole derivatives or heteroarenes under aerobic conditions with the FeBr 3 catalyst (Li group, Scheme 1B), 17 graphene oxide (Su), 18 and copper catalysts (Kozlowski).…”
Section: ■ Introductionmentioning
confidence: 99%